Building Virtual Private Server In Net-Centric Computing Laboratory - Aris Kurniawan Yusuf; Ade Hendri Hendrawan; Yuggo Afrianto (Jurnal Teknik Informatika C.I.T Medicom, 2019)
The use of server computers in an institution is managed according to required needs and functions. But as time goes on the server needs to increase. The NCC Laboratory as a research laboratory requires a server management mechanism for utilities that have a private server space to support each of its research. Server researchers, currently running on the computer's respective physical server so that the emergence of limitations of the availability of physical server computers to new researchers, while the utility computer server researchers who have already run in the taste still the operating system. Therefore the purpose of this research is to build a VPS (Virtual Private Server) system in one computer for the personal space of researchers to manage the research content in the form of Web-based applications. The methods used in this study were experiments with stages of analysis, design, implementation, and testing. The operating system used is Linux Proxmox as virtual Manager, Ubuntu and CentOS as VPS. The result of this research VPS can be applied to support the needs of researchers using Linux operating system Ubuntu server and CentOS-based virtual manager Proxmox.